Age-specific survival in an English Twite Linaria flavirostris population - Gkourtsouli-Antoniadou, Ismini; Ewing, Steven R.; Hudson, George; Pearson, Michael A.; Schroeder, Julia; Welch, Peter E.; Wilkinson, Nicholas I.; Dunning, Jamie (Bird study, 2023)
Low juvenile survival may be one driver underpinning recent declines in one of England's remnant breeding Twite Linaria flavirostris populations, but declines are more likely driven by factors affecting all age groups.